Behaviour of Asphalt Mixtures with Recycled Polyethylene Terephthalate and High Density Polyethylene Pellet as Fine Aggregate Replacement - Wan Mohd Nazmi, Wan Abdul Rahman; Achmad Fauzi, Abdul Wahab; Siti Noorain, Zulkifly (2014)
The main objective of this study is to evaluate the behaviour of asphalt mixtures with recycled Polyethylene Terephthalate (PET) and High Density Polyethylene (HDPE) as fine aggregate replacement. The modified asphalts were determined by engineering properties of asphalt such as stiffness, permanent deformation and fatigue behaviour using Asphalt Testing System. The percentage of recycled PET and HDPE replace fine aggregate in asphalt mixture start up 25% percent. The recycled plastic subsitute aggregate of sieve size aggregate from 1.18 to 3.36mm content as follow with hot mix asphalt wearing course 14 (ACW14) in Standard Specification of Public Work Department of Malaysia. The bitumen content of asphalt mixture was 5.5% of weight of asphalt mixture. The Repeated Load Axial Test(RLAT), Indirect Tensile Stiffness Modulus Test (ITSM) and Indirect Tensile Fatigue Test (ITFT) were used to determine the permanent deformation, stiffness and fatigue properties of asphalt, respectively. In stiffness aspect, the result shows that all PET modified asphalt is less stiff than unmodified asphalt. All HDPE modified asphalts are stiffer rather than unmodified asphalt except 25% HDPE modified asphalt. In term of permanent deformation via RLAT, all modified asphalt slightly resists axial strain compare to unmodified asphalt. In ITFT view, the unmodified asphalt is more resistant to fatigue rather than HDPE modified asphalt except 10% of HDPE modified asphalt. The 5% and 15% PET modified asphalt are more resistant to fatigue compare to unmodified asphalt. In conclusion, the 10% HDPE modified asphalt could consider comply with all engineering properties requirement.